KAJIAN BUAH SRIKAYA TENTANG PROSPEK DAN KOMODITAS UNGGULAN DI KABUPATEN SUMENEP - Dewi, Shendy Maudina; Parsudi, Setyo; Hidayat, Syarif Imam (Berkala Ilmiah AGRIDEVINA, 2020)
Apple sugar is a tropical fruit that was developed in order to increase fruit production. In Sumenep District, a lot of apple sugar are cultivated, but generally they have not been well developed, although there are quite a lot of enthusiasts. This study aims to analyze the prospects and commodities of apple sugar as the leading commodity in Sumenep District. The research location was chosen purposively in 3 sub-districts in Sumenep District, Saronggi District, Talango District, and Sumenep City District, which are producing Srikaya fruit. The type of data used is primary data and secondary data. Data analysis methods in this research are qualitative descriptive analysis and Location Quotient (LQ) analysis. Prospects are examined using primary data through in depth interviews with informants using purposive and snawball techniques, while superior commodities are examined using LQ analysis. The results showed that apple sugar  in Sumenep Regency has a promising prospect because of the potential of natural resources possessed was very supportive and the availability of a potential market with many requests from within and outside the region. Based on LQ analysis, for five consecutive years the LQ value of apple sugar is always more than 1. This means that apple sugar is classified as a superior commodity where production is not only able to meet their own needs but can also be distributed to other regions outside Sumenep District. DOI : https://doi.org/10.33005/adv.v9i1.2188